Manajemen Strategi Komunikasi Pemasaran Waroeng Baper Pekanbaru - Abdillah, Rizky; Sukri, Al (The Journal of Communication Management and Organization, 2022)
Waroeng Baper Pekanbaru is often discussed about a new concept café with crowded visitors and always holds events and live music. This study aims to determine the marketing communication strategy in increasing visitors to Waroeng Baper Pekanbaru. This study used qualitative research methods. The subjects in this study were Human Resource Development of Waroeng Baper Pekanbaru, Marketing Cafe Waroeng Baper Pekanbaru and five visitors of Waroeng Baper Pekanbaru. The results showed that the communication strategy carried out consisted of: Recognizing the communication target, the frame of reference factor, the situation and condition factor, the selection of communication media, the assessment of the purpose of the communication message, the attractiveness of the source and the credibility of the source. has implemented an effective and optimal.